Perdagangan Arab dan Kedatangan Islam ke Nusantara: Rekonstruksi Pemikiran Orientalis - M. Desta Ramadoni; Badrun Badrun (Local History & Heritage, 2022)
Debating the arrival of Islam in the archipelago, many historians have their own views and arguments. Arab trade in the archipelago has left very clear traces. This trace is compared as evidence of the early emergence of Islam. Thomas W. Arnold, John Crawfurd, L. W. C Van den Berg and Michael Laffan are figures who have the opinion that Arab traders had an important role in the process of entering Islam in the archipelago. This research is a theoretical study with the concept of library research which reconstructs the thoughts and views of these figures to see the influence of Arab traders in the archipelago. Even in the 2nd century BC Arab traders traded with Sri Lanka. The trading ability of the Arabs then solidified their dominance in the West-Eastern trade world which has intensified since the 7th century AD. Although some experts doubt the ability of Arab traders and their relations in the spread of Islam, Arab trading activities have been able to contribute to the Islamic world in the archipelago.